2020
DOI: 10.3389/fmed.2020.598272
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Mortality and Morbidity in COVID-19 Positive vs. COVID-19 Negative Individuals and vs. Individuals Tested for Influenza A/B: A Population-Based Study

Abstract: Background: As of October 2020, COVID-19 has caused 1,000,000 deaths worldwide. However, large-scale studies of COVID-19 mortality and new-onset comorbidity compared to individuals tested negative for COVID-19 and individuals tested for influenza A/B are lacking. We investigated COVID-19 30-day mortality and new-onset comorbidity compared to individuals with negative COVID-19 test results and individuals tested for influenza A/B.Methods and findings: This population-based cohort study utilized electronic healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“… 12 In another observational study investigating the initial symptoms of COVID-19, neurological symptoms were found in 9.7% of the patients. 48 In another study, the onset of anosmia was noted early in 73% of the patients prior to the diagnosis of COVID-19. 49 In addition, severe neurological manifestations, including altered mental status, stroke, and Guillain-Barré syndrome, could be the first symptom of COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“… 12 In another observational study investigating the initial symptoms of COVID-19, neurological symptoms were found in 9.7% of the patients. 48 In another study, the onset of anosmia was noted early in 73% of the patients prior to the diagnosis of COVID-19. 49 In addition, severe neurological manifestations, including altered mental status, stroke, and Guillain-Barré syndrome, could be the first symptom of COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…Globally, the Corona Virus Diseases 2019 (COVID-19) has imposed enormous burdens of morbidity and mortality among the general population. 1 Evidence shows that COVID-19 caused more than 2.5 million deaths globally. 2 The risk of dying were higher among older adults and people who had chronic medical related disease such as lung cancer, asthma, type 2 diabetes mellitus, heart diseases, and immune compromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, in reviews of Covid-19 publications, reported clinically and autopsy-determined rates of acute brain infarction range from 0.5% to 20% while rates of acute brain hemorrhage range from 0.13% to 9.5% 45-78 . A small number of clinical studies have also compared rates of stroke in hospitalized patients with Covid-19 versus influenza, with two studies finding increased rates with Covid-19 74,75 (1.6% vs 0.2% and 0.9% vs 0.3%) and one finding equivalent rates 45 T(1.2% for both). As these rates are all much smaller than what we have found here and as clinical detection of both stroke and pneumonia is poorly sensitive compared to autopsy 79-83,95 , the overall likelihood is that Covid-19 pneumonia and non-Covid-19 pneumonia may have similar risks tor concurrent acute brain infarction and acute brain hemorrhage when pneumonia is severe enough to cause death, and stroke overall may not be differentially prevalent in subjects dying with either type of pneumonia or non-Covid-19 pneumonia as compared to subjects dying from other causes.…”
Section: Discussionmentioning
confidence: 99%